Analisis Kebutuhan Luas Apron dan Terminal Penumpang Bandara Internasional Lombok untuk Menunjang Kegiatan Pariwisata serta Kawasan Ekonomi Khusus (KEK) - Adita Utami; Muhammad Tjipta Rafie Rahmanditya (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2023)
This study discusses the needs of passenger terminals and aprons at Lombok International Airport in the next 10 years, namely 2032 taking into account the conditions of the covid-19 pandemic with the aim of predicting the needs of passenger terminals and aprons of Lombok International Airport with the potential for tourism and Special Economic Zones. The method used is a combination of time series and econometric analysis to perform forecasting. This study was conducted using 2 scenarios in the analysis of the calculation of apron needs. The results of this study are in the form of the capacity of the existing apron able to serve peak hour conditions with 24 operations / hour. Based on forecasting in 2032, it is predicted that there will be 42,236 aircraft movements with a peak hour volume of 27 operations /hour and there will be 4,688,824 passengers with a peak hour volume of 1,904 people. then, there will be an expansion of the apron area for scenario 1 of 552 m2 with 17 parking stands and scenario 2 of 26,514 m2 with 23 parking stands and expansion of the passenger terminal facility area.